TINJAUAN SIFAT-SIFAT MEKANIK BETON ALIR MUTU TINGGI DENGAN SILIKA FUME SEBAGAI BAHAN TAMBAHAN - Sebayang, Surya (Rekayasa : Jurnal Ilmiah Fakultas Teknik Universitas Lampung, 2011)
Flowing concrete flow under it own weight and maintain homogeneity while filling and passing around congested reinforcement. Flowing concrete is used to reduce or eliminate the need formvibration to reduce construction cost and reducing construction time. High strength flowing concrete in this research used silica fume as additive material in flowing concrete. The properties investigated are workability, concrete setting time, and compression strength. Proportion ofmaterial for concrete determined according to ACI 211-4R-1993 and combine with Hashimoto method. The addition of silica fume to the concrete are 0 %, 3%, 6%, 9%, 12% and 15% of the cement content. The test result indicated that effect of silica fume in fresh concrete was reduced the workability of the concrete. Addition of silica fume was made fresh concrete enough cohesiveness without causing segregation. Addition of silica fume was increased the initial andfinal setting time. The cylinder compression strength of silica fume flowing concrete at 7day,14 days, and 28 day was higher than compression strength of flowing concrete without silica fume at the same days. The optimum strength of silica fume flowing concrete was 51,35 MPa at 56 days age, in 9 % presence of silica fume.